The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.25121/mr.2018.21.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Badanie fizykalne stosowane przez pielęgniarki na wybranych oddziałach szpitalnych

Abstract: Introduction. The history of the use of physical examination by nurses in the United States of America dates back to the 1960s. Transformation of nurses’ education and midwives in Poland also enabled the introduction of classes preparing students and nurses for physical examination. Aim. The aim of the study was to assess the scope of physical examination used by nurses in selected surgical and non-surgical departments. Material and methods. The study involved 89 nurses employed in one of the hospitals in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…This examination is also performed on bedridden patients. Mędrzycka-Dąbrowska et al [17], after analysing their own research, concluded that nurses working in surgical wards perform physical examinations more often, compared to nurses from conservative wards. The examinations include measuring blood pressure, heart rate, respiration, and during hospital admission.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This examination is also performed on bedridden patients. Mędrzycka-Dąbrowska et al [17], after analysing their own research, concluded that nurses working in surgical wards perform physical examinations more often, compared to nurses from conservative wards. The examinations include measuring blood pressure, heart rate, respiration, and during hospital admission.…”
Section: Resultsmentioning
confidence: 99%
“…Our own research has nations as sufficient, 38.2% as good, and just over 10% as insufficient. It is also worth noting that 39% of respondents were willing to improve their knowledge with a course or training [17]. The results of Liyew et al showed that nurses working in intensive care units had good practice in physical assessment among seriously ill patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…Historia badania fizykalnego prowadzonego przez pielęgniarkę sięga lat 60. XX wieku [5]. Podstawową metodą gromadzenia danych na temat pacjenta jest ocena jego stanu zdrowia.…”
Section: Ocena Stanu Pacjentaunclassified
“…Z ich badań, prowadzonych na terenie województwa pomorskiego, wynika, że pomiary parametrów życiowych, ocenę budowy ciała i stanu odżywienia częściej wykonują pielęgniarki na oddziałach zabiegowych w porównaniu z jednostkami niezabiegowymi. Ponadto poziom wykształcenia i staż pracy istotnie wpływają na częstość wykonywania badań fizykalnych [5]. Takie zależności nie wynikają bezpośrednio z prezentowanych wyników, prawdopodobnie z uwagi Wśród barier ograniczających wykonywanie badań fizykalnych w praktyce klinicznej wymieniane są: kwestie osobiste (stres i lęk przed wykonywaniem badań spowodowany brakiem pewności siebie, brak gotowości wynikający z małego doświadczenia klinicznego), przeszkody związane z edukacją (rozbieżności pomiędzy teorią a praktyką, ograniczone możliwości doskonalenia umiejętności zdobytych podczas zajęć symulacyj-nych w czasie studiów w warunkach klinicznych, niskie kompetencje instruktorów, nieodpowiednie programy nauczania), wyzwania związane z praktyką kliniczną (marginalizowanie umiejętności i kompetencji do wykonywania badań fizykalnych przez pielęgniarki w praktyce klinicznej, brak wpływu na opiekę nad chorym) [13].…”
Section: Omówienieunclassified
See 1 more Smart Citation